2007
DOI: 10.1021/la063654f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stabilizer on Formation of “Onionlike” Multilayered Polystyrene-block-poly(methyl Methacrylate) Particles

Abstract: The effect of the kind of stabilizers on the formation of "onionlike" multilayered polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) particles was studied. The release of toluene from PS-b-PMMA/toluene droplets dispersed in aqueous medium resulted in the formation of onionlike multilayered structures in the particles for all stabilizers used. However, the surface composition of the particles was strongly affected by the kind of stabilizer. When sodium dodecyl sulfate (SDS) and poly(vinyl alcohol) (PVA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…In this context, controlled radical polymerization, including the three different methods (nitroxide-mediated radical polymerization (NMP) [1], atom transfer radical polymerization (ATRP) [2] and reversible addition fragmentation chain-transfer polymerization (RAFT) [3]), has in the past years emerged as a technique of choice to prepare block, graft or comb copolymers of precise molecular and chemical structure. These types of polymers are increasingly involved in traditional structural materials [4] as well as in higher added value applications such as core-shell functional nanoparticles [5], organic/inorganic nanoparticles [6] or block copolymer lithography [7,8]. For the development of materials with unique combinations of properties, the self-assembling capability of block copolymers and the resulting regular nanostructures are indeed highly appreciated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, controlled radical polymerization, including the three different methods (nitroxide-mediated radical polymerization (NMP) [1], atom transfer radical polymerization (ATRP) [2] and reversible addition fragmentation chain-transfer polymerization (RAFT) [3]), has in the past years emerged as a technique of choice to prepare block, graft or comb copolymers of precise molecular and chemical structure. These types of polymers are increasingly involved in traditional structural materials [4] as well as in higher added value applications such as core-shell functional nanoparticles [5], organic/inorganic nanoparticles [6] or block copolymer lithography [7,8]. For the development of materials with unique combinations of properties, the self-assembling capability of block copolymers and the resulting regular nanostructures are indeed highly appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Okubo et al reported two main approaches to prepare nanostructured polymer particles [6,10,11,12]. In the first approach, multilayered polystyrene/poly(methyl methacrylate) composite microparticles were prepared by the so-called solvent-absorbing/releasing method [6,10,11], using either graft copolymers (polystyrene- g -polymethyl methacrylate) or block copolymers (polystyrene- b -polymethyl methacrylate) as compatibilizers. In the second approach, they used two-step ATRP miniemulsion polymerization process to prepare poly( i -butyl methacrylate)- b -polystyrene nanostructured latex particles [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, because methods for modifying the surfaces of such confining geometries have not been well-developed, many studies have not considered wall effects. [20][21][22] This is especially true of confining geometries with a mobile interfacial boundary, in which the dynamics of the interface may affect the shape of the confining geometry as well as the internal phase morphology. Here, we explored the interface-driven morphological evolution of a symmetric diblock copolymer of polystyreneblock-polybutadiene (PS-b-PB) confined in oil-in-water emulsion droplets.…”
mentioning
confidence: 99%
“…Half-spherical structures are accessible by removing the liquid in acorn structures formed with a polymer and a liquid [40,61]. Onion-like structures are created from block copolymers, for which the phase separation into lamellae causes layered structures that follows the curvature of the particle where they are confined [37,40,62]. The diameter of the particle is in this case also very important.…”
Section: Colloidal Structuresmentioning
confidence: 99%